2022
DOI: 10.1021/acs.langmuir.2c00852
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Kilogram Carbon Dots for Superior Friction Reduction and Antiwear Additives

Abstract: Because of the high synthesis cost, strong chemical inertness, complex process, and easy to endanger environment of traditional carbon-based nanolubricant additives, the development of its application in lubrication is limited. Therefore, a new type of lubricant additive with low cost, high yield, high performance, and environmental protection is urgently needed. Herein, a kilogram-scale carbon dots (CDs) lubricant additive was prepared by a simple and green one-step reaction of aldol condensation, which showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…The kinematic viscosity was equal to the ratio of dynamic viscosity and density, so the dynamic viscosity of the two dispersions was η 1 = 6.15 × 10 –2 Pa·s (SFO 1 wt %) and η 2 = 20.21 × 10 –2 Pa·s (PAO10 0.12 wt %). Also, u = 62.8 mm/s, fixed sphere radius ( R ) = 2 mm, applied loads W 1 = 3 N and W 2 = 1 N, k approximately 1, and E ′ = 233 GPa …”
Section: Tribological Performance Test Of Ncdsmentioning
confidence: 99%
See 2 more Smart Citations
“…The kinematic viscosity was equal to the ratio of dynamic viscosity and density, so the dynamic viscosity of the two dispersions was η 1 = 6.15 × 10 –2 Pa·s (SFO 1 wt %) and η 2 = 20.21 × 10 –2 Pa·s (PAO10 0.12 wt %). Also, u = 62.8 mm/s, fixed sphere radius ( R ) = 2 mm, applied loads W 1 = 3 N and W 2 = 1 N, k approximately 1, and E ′ = 233 GPa …”
Section: Tribological Performance Test Of Ncdsmentioning
confidence: 99%
“…The preparation of CD lubricating additives has been reported in our previous work. 24 In short, acetaldehyde (CH 3 CHO) and sodium hydroxide (NaOH) directly undergo aldol condensation reaction to prepare CD lubricating additives.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the diverse inorganic nanoadditives, the CDs are lately becoming the most attractive additives owing to their regular morphology, small but uniform particle size, high chemical stability, and strong film-building ability. As most CDs have been synthesized by the bottom-up method, abundant target groups could be facilely grafted on the surfaces of CDs during the synthesis processes. Based on this merit, the long-term dispersion stability of CDs in polar and partially polar base oils has been perfectly resolved. However, the research studies on CDs as additives of nonpolar base oil of PAO were far from enough since the synthesis and extraction of CDs modified by totally nonpolar groups were especially difficult . To avoid the abovementioned tedious and even polluting chemical modification process, the amphiphilic CDs were conveniently dispersed into PAO as additives by using Span-80 as dispersant .…”
Section: Introductionmentioning
confidence: 99%
“…Grease can stick better than lubricating oils through their excellent adhesion on frictional interfaces where gravity and centrifugal force cause serious loss. , Recently, the continuous development of productivity has required a higher grease performance. It has been confirmed that the addition of lubricant additives may enhance their tribological properties. The dispersibility of nanoadditives is the most critical factor to influence their performance in lubricants, and chemical functionalization is the most common method to improve its dispersibility. Ismail et al performed a reaction at 80 °C for 24 h and successfully grafted the straight alkyl chain onto graphene oxide to enhance its hydrophobicity and tribological properties in lubricants. In addition, the functionalized additive has excellent lipophilic properties and improves the solubility of the additive in the oil .…”
Section: Introductionmentioning
confidence: 99%